'Rapid counseling': counseling with music that can reduce anxiety about thesis in just one session - Oentarto, Aloysius Selo Aryobimo; Gading , I Ketut; Lestari, Luh Putu Sri (COUNS-EDU: The International Journal of Counseling and Education, 2024)
Every student will undergo their education with the difficulties they will experience, and every student will experience a thesis or final project which is one of the requirements for a student to be considered a graduate. When carrying out a thesis, the average student will experience anxiety, and anxiety regarding the thesis can be said to be academic anxiety. Academic anxiety is a feeling of fear, danger, and fear due to the pressure of the education being pursued. Rapid counseling is a method of therapeutic assistance that is carried out quickly, with just one meeting, and can be carried out individually or in groups. and can be combined with music. The aim of this research is to determine the effectiveness of Rapid Counseling with Single-Session Music Therapy to reduce anxiety about the thesis in three Atma Jaya Counseling Guidance Students. The subjects of this research were three female students from the class of 2019 who were taking a thesis and had a high level of academic anxiety. This research is a quantitative experimental research with a single subject design. The interview data collection technique and assessment scale instrument constructed by Situmorang is the Academic Anxiety Scale which has a total of 24 items with a validity result of 0.268 and a reliability of 0.961. In the implementation of Rapid Counseling with Single-Session Music Therapy, it can be effective in reducing anxiety about the thesis with just one meeting session and can provide the counselee with a "soundtrack of my life" that has been made together with the counselor during the counseling service so that when anxiety about the thesis is high again, the counselee only needs to listen to the song that has been made together with the counselor.